Inhibition of Protein Kinase Mζ Disrupts the Stable Spatial Discharge of Hippocampal Place Cells in a Familiar Environment - Barry, Jeremy M. (Society for Neuroscience, 2012)
It is widely held that spatial computations in the rodent hippocampus require the location-specific discharge of place cells that together form a stable cognitive map used to solve and perform spatial tasks. It is not known, however, if map stability requires persistent hippocampal synaptic strength changes that are vulnerable to blockade of protein kinase Mζ (PKMζ) phosphorylation activity, a manipulation that reverses hippocampal LTP and disrupts multiple forms of long-term memory. Here we report that acute intrahippocampal inhibition of PKMζ disrupts place cell activity in a familiar environment, where the map is expected to be stable. After this disruption, new, stable spatial firing patterns can later form, but the new and original maps are unrelated even though the rat is exposed to a constant environment. We therefore propose that the previously demonstrated erasure of stored spatial memory and the disruption of place cell firing are parallel effects of PKMζ blockade. We similarly propose that the known sparing of new spatial memory formation depends on the sparing of new map formation. On these bases, we argue that the loss of the map used to perform a practiced spatial task leads to behavioral performance deficits, and that synaptic plasticity maintained by PKMζ, which stabilizes the map, is essential for the proper expression of spatial memory.